Информационная система измерения и контроля параметров воздушной среды - Костенко, Виталий Леонидович; Кондратьев, Сергей Борисович; Ядрова, Марина Васильевна; Попов, Дмитрий Александрович (НТУ "ХПИ", 2017)
В статье представлены результаты исследований по созданию информационно-измерительной системы контроля параметров воздушной среды и обеспечения комфортного состояния человека. Показана возможность повышения эффективности системы – расширения функциональных возможностей, снижения энергопотребления в автономном режиме, массогабаритных показателей и стоимости, за счет использования современной элементной базы, в том числе микроконтроллера STM32F 100. Приведены результаты разработки программного обеспечения микроконтроллера и визуализации параметров на мониторе. Результаты исследования могут иметь практическое применение при контроле и регулировании параметров воздуха и обеспечения комфорта в помещениях.

The article presents the results of studies on the creation of an information and measuring system for controlling air parameters and ensuring a comfortable human condition. Based on the analysis of known information on the air quality monitoring devices on the market, the possibility of improving the efficiency of such devices based on modern components of information and measurement equipment and microcontrollers STM32F 100 is shown. Since the measurement of individual air parameters does not allow to provide such important indicators as the comfort of the environment and the informative nature of the results, special attention is paid to the expansion of the system's functionality in the framework of the system approach. The possibility of increasing the efficiency of the system is shown – the expansion of functionality, the reduction in power consumption in standalone mode, the mass-dimensional parameters and the cost of components compared to the known ones, due to the use of the STM32100 microcontroller and the modern element base. The results of the software development of the microcontroller based on the IDE Coocox platform. The main algorithm includes the interrogation of sensors, keyboards, the output of measurement results on the display and the color indicator, data processing and decision-making for switching on and off two or more relays for ventilation and air conditioning control. For visualization of parameters on the computer screen in the form of graphs, EXCEL tables, accumulation of a large amount of statistical data in the long-term analysis, the microcontroller is connected to a personal computer (PC) via a USB port for additional statistical processing of the received data. The front panel on the PC screen, created in the software package LabView. The results of the study can have practical application in controlling and regulating air and providing comfort in the premises.
Information system of measurement and control parameters of the air framework
Keywords: микроконтроллер; код программы; датчик; эффективность; персональный компьютер; ПК; air environment; microcontroller